Recognition of membership in the IUCN/SSC Tortoise and Freshwater Turtle Specialist Group, 2004-2008 - Indraneil, Das (Universiti Malaysia Sarawak, (UNIMAS), 2008)
Recognition of membership in the IUCN/SSC Tortoise and Freshwater Turtle Specialist Group, 2004-2008 Quadrennium for contributions to Turtle Biology and Conservation